Implementation of Flipped Classroom Model to Improve Students' Academic Achievement in Teluk Bintuni - Putra, Deva; Sandi, Renda (Research Collaboration Community (RCC), 2025)
Implementation of the Flipped Classroom model in improving students' academic achievement in secondary schools in Teluk Bintuni, especially in science and mathematics subjects. The method used is an experimental design with a quantitative approach, namely the pretest-posttest control group. The experimental group used the Flipped Classroom model, while the control group followed traditional learning. The results showed that the Flipped Classroom model improved students' academic achievement with an average score increase of 30% in the experimental group, compared to 14% in the control group. However, the main challenge faced is the limited access to technology and adequate infrastructure in the area. These findings indicate that Flipped Classroom can be an effective learning alternative, as long as adequate technological support and training for teachers are provided